1999
DOI: 10.1289/ehp.99107s6823
|View full text |Cite
|
Sign up to set email alerts
|

Summary: workshop on health risks attributable to ETS exposure in the workplace.

Abstract: This 1998 workshop was convened to address the health risks of exposure to environmental tobacco smoke (ETS) in the workplace. It was paired with a 1997 workshop on issues related to ETS exposure in work environments (1). In the 1998 workshop, a multidisciplinary group of participants was charged with reviewing evidence on the quantitative risks to health posed by ETS and to discuss development of risk assessment methodology for the future. The overall charges for the present workshop were * to consider variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…A more current example concerns the health risks attributable to exposure to environmental tobacco smoke at work (316). In 2000, an amendment of the Tobacco Control Act came into force in Finland.…”
Section: Prevention Of Work-related Diseasesmentioning
confidence: 99%
“…A more current example concerns the health risks attributable to exposure to environmental tobacco smoke at work (316). In 2000, an amendment of the Tobacco Control Act came into force in Finland.…”
Section: Prevention Of Work-related Diseasesmentioning
confidence: 99%
“…There is an increasing body of evidence that ETS increases the risk of e.g., cardiovascular diseases, asthma, and lung cancer [Jaakkola and Samet, 1999b;Ducatman and McLellan, 2000]. In Finland, it has been estimated that in 1996 about 250 fatalities were due to ETS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…There is convincing evidence that ETS causes lung cancer and coronary heart disease, both of which are diseases of the elderly [8,[32][33][34][35]. Several cross-sectional studies have shown increased occurrence of chronic respiratory symptoms and deficits in ventilatory lung function in relation to ETS exposure at home and/or at work [8,13,28,32,[36][37][38][39][40].…”
Section: Health Effects Of Respirable Suspended Particles Nitrogen Dmentioning
confidence: 99%